2017
DOI: 10.3389/fpls.2016.01972
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and Genotypic Variation in Leaf Wax Content and Composition, and in Expression of Wax Biosynthetic Genes in Brassica oleracea var. capitata

Abstract: Cuticular waxes act as a protective barrier against environmental stresses. In the present study, we investigated developmental and genotypic variation in wax formation of cabbage lines, with a view to understand the related morphology, genetics and biochemistry. Our studies revealed that the relative expression levels of wax biosynthetic genes in the first-formed leaf of the highest-wax line remained constantly higher but were decreased in other genotypes with leaf aging. Similarly, the expression of most of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…Wax composition and content can vary according to species, ontogeny, and environment ( Jenks and Ashworth, 1999 ; Laila et al, 2016 ). As noted previously, the major components of wax are VLCFAs and their derivatives, including alkanes, aldehydes, primary and secondary alcohols, ketones, and esters ( Riederer and Müller, 2006 ; Bernard and Joubès, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wax composition and content can vary according to species, ontogeny, and environment ( Jenks and Ashworth, 1999 ; Laila et al, 2016 ). As noted previously, the major components of wax are VLCFAs and their derivatives, including alkanes, aldehydes, primary and secondary alcohols, ketones, and esters ( Riederer and Müller, 2006 ; Bernard and Joubès, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The tomentose leaf surface could also be a main factor contributing to lowering cuticular transpiration when water supply was low. Under drought stress, instead, B. macrocarpa maintained the lowest leaf temperatures, possibly explained by a combination of leaf reflection due to higher presence of waxes on the epidermis that reduces also cuticular water loss (Holmes and Keiller 2002;Laila et al 2017) and the higher water content, confirmed by higher RWC and less negative Ψ L.…”
Section: Discussionmentioning
confidence: 95%
“…But, nonadecane was predominant alkane in seed coat surface waxes of BIO L 212 Ratan and Nirmal B-1 (Adhikary et al ., 2014); whereas palmitoleic acid, and palmitic acid and lauric acid were the most abundant free fatty acids in seed coat surface waxes of BIO L 212 Ratan and Nirmal B-1, respectively (Adhikary et al ., 2016). The present study revealed that the composition of n -alkanes and free fatty acids in surface waxes of plants might vary between plant species as well as within different cultivars of a plant species including various parts of a plant species (Piasentier et al ., 2000; Dodoš et al ., 2015; Wang et al ., 2015; Laila et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%